2019
DOI: 10.1596/1813-9450-8818
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in the Quality of Health Services: Wealth, Content of Care, and Price of Antenatal Consultations in the Democratic Republic of Congo

Abstract: Using unique direct observations of patient-provider interactions linked to patient exit interviews and detailed household surveys, this paper assesses the relationship between patient wealth and the quality and price of antenatal care in the Democratic Republic of Congo. Overall, the analysis finds a significant wealth-quality gradient, with a standard deviation increase in wealth being associated with an increase of 4 percentage points in protocol compliance. This increase in compliance represents 8 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Tanzania, a study conducted in the Arusha region found that the competence of doctors in both private and public sectors was significantly lower in poorer regions [ 18 ]. One study conducted in the Democratic Republic of Congo found that women with lower socio-economic status lived in areas where the quality of care available was low compared to women with higher SES [ 14 ]. Two studies looked at the effect of pay-for-performance (P4P) schemes on inequalities in the performance of providers in Tanzania and Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, a study conducted in the Arusha region found that the competence of doctors in both private and public sectors was significantly lower in poorer regions [ 18 ]. One study conducted in the Democratic Republic of Congo found that women with lower socio-economic status lived in areas where the quality of care available was low compared to women with higher SES [ 14 ]. Two studies looked at the effect of pay-for-performance (P4P) schemes on inequalities in the performance of providers in Tanzania and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have looked at this type of inequality, perhaps reflecting the rarity of having data on both quality of care and catchment population SES in the same geographical area. The available studies indicate consistent evidence that areas with low SES tend to be served by providers with lower competence [ 5 , 9 , 11 , 14 , 16 , 18 ] and by facilities with limited equipment and infrastructure [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence demonstrates that this is not the case; individuals with different characteristics receive different quality of care. 5 14 Estimates of inequalities in effective coverage measures that are derived from linked household and facility data are driven only by the access to care measure.…”
Section: Facility-level Data Do Not Include the Individual Data Neede...mentioning
confidence: 99%
“…Exact-match linking of individuals in population data to the exact health facility they attended will capture systematic differences in care-seeking behaviour between individuals with different characteristics—for example, that wealthier individuals are more likely to bypass their nearest sources of care to seek higher quality care—either outside of their catchment area or at a higher level facility. 5 15 Ecological linking—in which individuals from population data are linked to an average quality score across multiple health facilities—takes us a step further away, since it assumes there are no systematic differences in care-seeking behaviour between individuals with different characteristics. Adjusting for the type of facility that people report receiving care from has been demonstrated to generate valid measures of effective coverage, as likely accounts for some difference in care-seeking behaviour.…”
Section: Facility-level Data Do Not Include the Individual Data Neede...mentioning
confidence: 99%
See 1 more Smart Citation